Malignant pleural mesothelioma forming a huge mediastinal mass and causing atrial fibrillation - Hiroko Kuwabara; Hiroshi Tsuji; Yuki Inada; Yuro Shibayama (Wolters Kluwer Medknow Publications, 2012)
A patient with malignant pleural mesothelioma was admitted with atrial fibrillation. Chest computed tomography showed a huge mediastinal tumor adjacent to the heart. Autopsy revealed a 12 × 9.5 -cm mediastinal mass involving the right lung, which distorted and stretched the myocardial sleeve surrounding the right inferior pulmonary vein. This case demonstrates that advanced malignant pleural mesothelioma can cause atrial fibrillation, possibly by stimulating myocardium around a pulmonary vein.